PERAN KELOMPOK TANI DALAM MENINGKATKAN PRODUKTIVITAS USAHATANI KENTANG DI DESA SUMBER BRANTAS KECAMATAN BUMIAJI KOTA BATU - Dwi Febrianty Nabila Wardani; Dwi Susilowati; Farida Syakir (Program Studi Agribisnis, 2019)
ABSTRACTEvery years, the demand of potatoes, population, income and potatoes processing industries are tends to increased. Production, land and potatoes's productivity are fluctuated from 2014 to 2017. Because of this problem, government should be concerned about agricultural development in Indonesia. In agricultural development, the farmers have important role. Therefore, empowerment of farming communities has to be done, so the farmers could handle any problems that occurs in their farm. One of government's programs to solve this problem is developing group of farmers in every villages. The aim of this research is to identify the role of farmer's group that influenced potatoes's productivity. Proportionate stratified random sampling is used for sampling method in this research. The research was conducted with 53 respondents. Those respondents are analyzed using frequency table and multiple linear regression. Frequency table results showed that the most important activity for farmer is routine meetings. Meanwhile, the activity that influenced potatoes's productivity (alfa = 0,10) are counseling, routine meetings and RDKK's forming. The using of subsidies fertilizer & excellent seeds are not influence potatoes's productivity.Keyword : potatoes, the role of farmer’s group.